The Role of the CDK4/6 Inhibitor Ribociclib in Locally Advanced and Oligometastatic Hormone Receptor Positive, Her2 Negative, Advanced Breast Cancer: Case Series and Review of the Literature - Botticelli, Andrea; Fabbri, Agnese; Roberto, Michela; Alesini, Daniele; Cirillo, Alessio; D’Auria, Giuliana; Krasniqi, Eriseld; Marrucci, Eleonora; Muratore, Margherita; Pantano, Francesco; Pizzuti, Laura; Portarena, Ilaria; et al. (Frontiers in Oncology, 2022)
The recent addition of cyclin-dependent kinase 4 (CDK4) and CDK6 inhibitors to endocrine therapy have remarkably improved the outcome of patients affected with hormone receptor positive (HR+), human epidermal grow factor receptor 2 negative (HER2 -) advanced breast cancer (ABC). Ribociclib showed to be effective across most subgroups, regardless of the number and the site of metastasis. Up to 10% of patients with ABC, reported an oligo-metastatic condition, recently defined as a slow volume metastatic disease with limited number and size of metastatic lesions (up to 5 and not necessarily in the same organ), potentially amenable for local treatment, aimed at achieving a complete remission status. Despite the wide use of CDK4/6 inhibitors in HR+, HER2-, ABC treatment, data regarding both locally advanced, inoperable disease and oligo-metastatic conditions are still poor. We reported a review and case series of HR+, HER2-, ABC patients treated with ribociclib as first-line therapy, for a locally advanced, and oligometastatic disease, reporting an impressive response and good safety profile.